Monoallelic loss of the F-actin-binding protein radixin facilitates startle reactivity and pre-pulse inhibition in mice - Hausrat, Torben J.; Vogl, Christian; Neef, Jakob; Schweizer, Michaela; Yee, Benjamin K.; Strenzke, Nicola; Kneussel, Matthias (Frontiers in Cell and Developmental Biology, 2022)
Hearing impairment is one of the most common disorder with a global burden and increasing prevalence in an ever-aging population. Previous research has largely focused on peripheral sensory perception, while the brain circuits of auditory processing and integration remain poorly understood. Mutations in the rdx gene, encoding the F-actin binding protein radixin (Rdx), can induce hearing loss in human patients and homozygous depletion of Rdx causes deafness in mice. However, the precise physiological function of Rdx in hearing and auditory information processing is still ill-defined. Here, we investigated consequences of rdx monoallelic loss in the mouse. Unlike the homozygous (-/-) rdx knockout, which is characterized by the degeneration of actin-based stereocilia and subsequent hearing loss, our analysis of heterozygous mutants has revealed a different phenotype. Specifically, monoallelic loss of rdx potentiated the startle reflex in response to acoustic stimulation of increasing intensities, suggesting a gain of function relative to wildtype littermates. The monoallelic loss of the rdx gene also facilitated pre-pulse inhibition of the acoustic startle reflex induced by weak auditory pre-pulse stimuli, indicating a modification to the circuit underlying sensorimotor gating of auditory input. However, the auditory brainstem response (ABR)-based hearing thresholds revealed a mild impairment in peripheral sound perception in rdx (+/-) mice, suggesting minor aberration of stereocilia structural integrity. Taken together, our data suggest a critical role of Rdx in the top-down processing and/or integration of auditory signals, and therefore a novel perspective to uncover further Rdx-mediated mechanisms in central auditory information processing.